The Effect of Fill Rate on Mechanical Properties of PLA Printed Samples - KAPTAN, Arslan; KARTAL, Fuat (Igdir University, 2020)
Three-dimensional (3D) printers are a rapidly developing technology used in many fields today. Polylactic acid (PLA) is one of the most researched and used biodegradable polymers to date. PLA stands out as a biomaterial in other industries due to its many benefits, as it replaces conventional petrochemical-based polymers. The main purpose of this study is; to investigate the effect of different fill rates (5%, 50% and 100%) on the mechanical properties of samples produced from PLA in 3D printers. For each filling ratio, 5 samples were produced for bending test defined by ASTM D-790 standard and tensile tests defined by ASTM D-638 standard. In this study, it is aimed to model a printer producing with stacking technology and to compare the effects of occupancy rate on mechanical properties in the modeled 3D printer.
Keywords: fused deposition modeling; D printer; polylactic acid (PLA); fused deposition modeling; Mechanical Engineering; D printer; Makine Mühendisliği; polylactic acid (PLA)